PENGARUH DEWAN PENGAWAS SYARIAH, GOOD CORPORATE GOVERNANCE TERHADAP KINERJA BANK SYARIAH INDONESIA - Mustion , Seppi; Ahmad Wira; Rozalinda (Jurnal Perbankan Syariah, 2024)
The research aims to examine the influence of the sharia supervisory board, Good Corporate Governance on the performance of sharia banks in Indonesia. The type of research used in this research is quantitative using secondary data. Data was taken from company financial reports and audited GCG implementation reports at Islamic banks in Indonesia during 2018-2022. In this research using a purposive sampling method, 10 out of 15 Sharia Commercial Banks can be used as samples. Data analysis to test the hypothesis used multiple linear regression and was processed using the SPSS version 25 program. The results of the research stated that the sharia supervisory board, Good Corporate Governance had an influence on the performance of sharia banks whose indicators used ROA. Partially, the sharia supervisory board has a negative and significant effect on ROA, GCG has a positive and significant effect on ROA. Meanwhile, the results of partial GCG testing have no effect on ROA as a proxy for Islamic bank performance. The influence of the sharia supervisory board on performance is measured according to the position of the DPS providing a strong view so that each DPS takes part in joint decisions with sharia banking institutions by implementing and improving financial performance. The DPS must provide continuous supervision of the performance of sharia banks to have good institutional strength so that stakeholders or sharia banking leaders evaluate performance according to sharia principles.